ATIVIDADE FÍSICA E SAÚDE NO CONTEXTO ESCOLAR: AS AULAS DE EDUCAÇÃO FÍSICA DO ENSINO MÉDIO NAS ESCOLAS PÚBLICAS ESTADUAIS DA CIDADE DE PONTA GROSSA/PR - Luz, Evenilson Silvestre da (2016)
This research has the object study the knowledge related to physical activity and health developed in the Physical Education classes of high school. The research is characterized like qualitative. The problematic question to be investigated is: What knowledge related to physical activity and health are developed in Physical Education high school? The questions that guide the research are: What are the theoretical and methodological assumptions related to physical activity and health appointed the Official Documents of Basic Education (BRAZIL, 1999, 2000, 2006; PARANÁ, 2008, 2012)? What are knowledge and habits of high school students related to physical activity and health? The research objectives were: a) Review the knowledge related to physical activity and health developed in Physical Education high school; b) Examine the theoretical and methodological assumptions related to physical activity and health appointed the Official Documents of Basic Education (BRAZIL, 1999, 2000, 2006; PARANÁ, 2008, 2012); c) Identify what are the knowledge and the habits of high school students related to physical activity and health. The theoretical basis of the research was substantiated by related studies: the assumptions of education for high school (SAVIANI, 1996, 1999; TONET, 2012a, 2012b, 2013; BRAZIL, 2013); the Physical Education in high school from the perspective of physical fitness and health (MOREIRA, 2001, 2006; PALMA, 2007; FINCK, 2010a, 2010b, 2014; RECK, 2012; CARRANO; DAYRELL, 2013; NAHAS, 2013; OLIVEIRA, 2014). The research methodology followed the parameters settled down by Cervo, 1983; Triviños, 1987; Marconi, Lakatos (2003); Barros, Lehfeld, 2007. The research was conducted in three (3) schools from public schools in the city of Ponta Grossa/PR, the participant‟s subjects were nine (9) Physical Education teachers who work in high school and three hundred ten (310) students of the 3rd year of high school. As research instruments were used document analysis, questionnaire and interview. The data will be systematized and analyzed according to the premises of Content Analysis (BARDIN, 2011). As results of the research show: The demand crescent for activities with low caloric expenditure and sedentary lifestyle statement, between the students of 3rd years of high school, are related to the lack of knowledge about the real benefits of physical activity for health; the potential choices of physical activities is associate with experiences lived by the students during the basic education; there are differences in the content proposition and knowledge for high school presented by Physical Education teachers pronouncing the gap in formation of the students of 3rd years of high school, which present difficulties to answer critically the appeals of the consumer and the media and the consequent adoption of healthy habits ruled the right to live well.